Risk Management of Zakat Management at BAZNAS Asahan - Zuhra Nahda; Ahmad Alfarezi; Muhammad Lathief Ilhamy Nasution (Penerbit Jurnal Indonesia, 2022)
Risk occurs in every organization or business activity. This also does not rule out the possibility of risk in the amil forum. The types of risks that may often occur in amil institutions are the risk of collecting zakat funds, the risk of managing zakat funds, and the risk of distributing zakat funds. The problem in this study is in the context of zakat management, where one thing that needs to be maintained is the credibility and accountability of zakat management institutions. Do not let people's distrust arise due to mistakes and violations in the management of zakat. Mistakes and violations in the management of zakat will have the potential to create a bad reputation for zakat institutions which will also cause fatal risks. there are risks that are directly related to using the performance of zakat institutions, for example errors in zakat distribution. There are risks that are indirectly related to the performance of zakat institutions but can have a quick impact, for example losing a professional amil.